Performance of Lime Kiln Dust as cementitious material - Latif M.A.; Naganathan S.; Razak H.A.; Mustapha K.N. (Elsevier Ltd, 2023)
Compressive strength; Density (specific gravity); Dust; Kilns; Lime; Mortar; Physical properties; Portland cement; Sustainable development; Cementitious materials; Engineering properties; Environmental problems; Hydration rate; Lime kiln dusts; Ordinary Portland cement; Setting time; Strength values; Strength of materials